Charge state distribution studies of pure and oxygen mixed krypton ECR plasma – signature of isotope anomaly and gas mixing effect. (23rd September 2016) - Kumar, Pravin; Mal, Kedar; Rodrigues, G.
Abstract : We report the charge state distributions of the pure, 25% and 50% oxygen mixed krypton plasma to shed more light on the understanding of the gas mixing and the isotope anomaly [A. G. Drentje, Rev. Sci. Instrum. 63 (1992) 2875 and Y Kawai, D Meyer, A Nadzeyka, U Wolters and K Wiesemann, Plasma Sources Sci. Technol. 10 (2001) 451] in the electron cyclotron resonance (ECR) plasmas. The krypton plasma was produced using a 10 GHz all‐permanent‐magnet ECR ion source. The intensities of the highly abundant four isotopes, viz. 82 Kr ( 11.58%), 83 Kr ( 11.49%), 84 Kr ( 57%) and 86 Kr (17.3%) up to +14 charge state have been measured by extracting the ions from the plasma and analysing them in the mass and the energy using a large acceptance analyzer‐cum‐switching dipole magnet. The influence of the oxygen gas mixing on the isotopic krypton ion intensities is clearly evidenced beyond +9 charge state. With and without oxygen mixing, the charge state distribution of the krypton ECR plasma shows the isotope anomaly with unusual trends. The anomaly in the intensities of the isotopes having quite closer natural abundance, viz. 82 Kr, 86 Kr and 83 Kr, 86 Kr is prominent, whereas the intensity ratio of 86 Kr to 84 Kr shows a weak signature of it. The isotope anomaly tends to disappear with increasing oxygen mixing in the plasma. The observed trends in the intensities of the krypton isotopes do not follow the prediction of linear Landau wave damping in the plasma. Copyright © 2016 John Wiley & Sons, Ltd.